A Series of Primary Alkylamine Borane Adducts CxH2x+1NH2BH3: Synthesis and Properties. Issue 37 (1st October 2021) - Turani‐I‐Belloto, Kevin; Valero‐Pedraza, María‐José; Chiriac, Rodica; Toche, François; Granier, Dominique; Cot, Didier; Petit, Eddy; Yot, Pascal G.; Alauzun, Johan G.; Demirci, Umit B.
Abstract: Primary alkylamine borane adducts Cx H2x+1 NH2 BH3 (CxAB) are unconventional molecules that may offer great opportunities in chemistry owing to their dihydrogen H δ+ ⋅⋅⋅H δ− bonds. Herein, we focus on six CxAB (x=4, 6, 8, 10, 12, 14), synthesized by Lewis acid‐base reaction between the complex (CH3 )2 S⋅BH3 and the primary alkylamines. At ambient temperature, C4AB and C6AB are oily liquid, and the other adducts are crystalline solids. The melting temperatures of the CxAB linearly increase as a function of ln(x) due to stronger intermolecular Van der Waals forces between the alkyl chains, and they are higher by 20–40 °C than those of the amines due to dihydrogen H δ+ ⋅⋅⋅H δ− bonds between the NH2 BH3 heads. The occurrence of dihydrogen H δ+ ⋅⋅⋅H δ− bonds is further confirmed by molecular and structural analyses. This is discussed hereafter. Abstract : Dihydrogen H δ+ ⋅⋅⋅H δ− bonds exist for the primary alkylamine borane adducts Cx H2x+1 NH2 BH3 (denoted CxAB; with x=4, 6, 8, 10, 12, 14). For instance, the crystal structures of C8AB to C14AB (monoclinic) show a close‐packed arrangement of the CxAB molecules where NH2 of one CxAB molecule is facing BH3 of another CxAB molecule, and the interactions between the NH2 BH3 heads are driven by dihydrogen H δ+ ⋅⋅⋅H δ− bonds.